Status Keluarga Sebagai Subyek Hukum dalam Pengurusan Harta Bersama - Perwitiningsih Perwitiningsih; Rikardo Simarmata (Universitas Airlangga, 2021)
This research is aimed at analyzing family status as legal subjects i.e. rights, wether husband and wife are considered as a legal subject or an independent individual subject. The discussion of this research is focused on the family as the legal subject in the management of joint assets. This research concludes that the family is one legal subject as member of marital assets. In law inforcement, family is a civil partnership between husband and wife who act as caretaker. marital assets are civil partnership assets. A family in taking legal actions against the joint assets must act with the consent of the husband and wife, and without mutual consent the transaction is null and void by law. Every transaction that is carried out by the husband or wife on behalf of the family and used for the benefit of the family becomes jointly and severally husband’s and wife’s responsibility if there is a loss from the transaction. A family civil partnership is not a legal entity because is does not fulfill the formal requirements as an Indonesian legal entity.Keywords: Family; Legal Subjects; Marital Assets. Penelitian ini bertujuan untuk menganalisis status keluarga sebagai subyek hukum, apakah suami-isteri sebagai keluarga dianggap satu subyek hukum atau masing-masing menjadi subyek hukum yang mandiri. Pembahasan difokuskan pada keluarga sebagai subyek hukum dalam pengurusan harta bersama perkawinan. Penelitian ini menyimpulkan bahwa keluarga dianggap satu subyek hukum dalam kaitannya sebagai subyek pemilikan harta bersama. Dalam lalu lintas hukum, keluarga merupakan sebuah persekutuan dengan suami-isteri yang bertindak sebagai pengurusnya. Harta bersama adalah harta persekutuan, keluarga dalam melakukan perbuatan hukum terhadap harta bersama harus bertindak atas persetujuan suami dan isteri, tanpa persetujuan satu sama lain transaksi tersebut tidak sah dan batal demi hukum. Setiap transaksi yang dilakukan suami atau isteri atas nama keluarga dan digunakan untuk kepentingan keluarga, maka suami-isteri bertanggungjawab secara tanggung renteng apabila terjadi kerugian yang ditimbulkan dari transaksi tersebut. Persekutuan keluarga bukan persekutuan yang berbadan hukum karena tidak memenuhi syarat formil sebagai badan hukum Indonesia.Kata Kunci: Keluarga; Subyek Hukum; Harta Bersama.